The Effect of Enterprise Risk Management and Financial Ratios on The Potential for Financial Distress and its Impact on The Firm Value of Pharmaceutical Companies Listed on The Indonesia Stock Exchange - Busyron Chudlori; Endang Etty Merawati; Nana Nawasiah (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the effect of Enterprise Risk Management and financial ratios, including liquidity, leverage, and profitability, on the potential for financial distress and its impact on firm value in pharmaceutical companies listed on the Indonesia Stock Exchange. This research uses a quantitative approach, involving data collection and statistical analysis to investigate phenomena and test the relationships between variables in a structured manner, focusing on Enterprise Risk Management, financial ratios, financial health, and firm value. The population of this study consists of 12 (twelve) pharmaceutical companies listed on the Indonesia Stock Exchange during the period 2016–2023. The sample was selected using purposive sampling, comprising 10 (ten) pharmaceutical companies that consistently published their annual and financial reports during the period 2016–2023. Data were collected through documentation and non-participatory observation methods. The secondary data used in this study were obtained from published audited financial and annual reports. The statistical analysis was conducted using the Structural Equation Modeling (SEM) method with Smart Partial Least Squares (PLS), operated through Smart PLS software version 4.1.0.9. The results indicate that Enterprise Risk Management, leverage, and financial distress have a positive and significant effect on firm value. On the other hand, liquidity has a negative and significant effect, while profitability shows a negative but insignificant effect on firm value. Additional findings related to financial distress show that liquidity and profitability have a positive and significant effect on financial distress as proxied by the Z-Score, where a higher Z-Score indicates a lower potential for financial distress.